The Maze Runner: Maze Runner, Book 1 - James Dashner, , Mark Deakins, (2009)
Book one in the blockbuster Maze Runner series that spawned a movie franchise and ushered in a worldwide phenomenon! And don’t miss The Fever Code, the highly-anticipated series conclusion that finally reveals the story of how the maze was built!